The low frequency ultrasonic wave caused cell lysis and modulated dielectrophoresis property in breast cancer cell line - Chinnawich Phamornnak (2018)
© 2014 IEEE. Various methods of cell manipulation have been applied for cancer treatment including ultrasonic manipulation like sonodynamic therapy and high intensity focus ultrasound (HIFU). The effects of ultrasonic wave are divided into 2 types; thermal and non-thermal effect, which is generated by high and low frequency respectively. Low frequency of ultrasonic manipulation is very interesting due to enhancement of cell poration. In this study, human breast cancer cell line (MDA-MB-231) is stimulated using low frequency ultrasonic wave. Two parameters were chosen; frequency and treatment time. The frequency of 70 and 100 kHz were generated by cup-shape probe and the treatment duration 15, 30, 45, 60, 75, 90, 105 and 120 min were employed. After ultrasonic exposure, the cell morphology was observed by microscope, the cell viability and number of cell were observed using trypan blue staining. Moreover, bioelectrical property of cell was determined by changing dielectrophoresis (DEP) phenomenon, which is determined in term of negative (nDEP) and positive (pDEP). The results showed the cellular debris and decreasing the amount of cell number can be observed at the duration 105 and 120 min of ultrasonic exposure times. On the other hand, the changing of DEP property is started at 15 min of ultrasonic exposure time. Therefore, these results confirm that the bioelectrical property of cell can be altered before biological behaviors are occurred. Finally, the nDEP property of cancer cell is modulated by low frequency ultrasonic wave. The tendency of nDEP is depended on exposure time and the long ultrasonic exposure time can make the cell lysis.